Novel method for combining microbial bioremediation with static magnetic fields to remediate mercury-contaminated soils - Naima Werfelli; Mariem Taboubi; Sirine Ridene; Hadir Bousselmi; Ahlem Mansouri; Ahmed Landoulsi; Chiraz Abbes (PLoS ONE, 2025)
Heavy metal contamination poses a significant risk to both the environment and public health, particularly through metallic mercury, a neurotoxic contaminant capable of bioaccumulating in food chains. This article presents a novel approach to remediating mercury-polluted soils by combining microbial bioremediation with the effects of a static magnetic field, applied at an induction of 260 mT for 12 hours at the start of the experiment. The decontamination technique was applied to mercury-contaminated soil bioaugmented with the bacterial strain Pseudomonas stutzeri LBR. Mercury remediation was enhanced by the static magnetic field in conjunction with bioaugmentation over a 30-day period. Notably, in non-sterile soils, the combination of an SMF, total soil flora, and Pseudomonas stutzeri LBR increased mercury remediation efficiency by 49.36%, compared to only 23.85% in the absence of an static magnetic field and soil bioaugmentation. Similarly, in sterile soils, the combination of an static magnetic field and Pseudomonas stutzeri LBR increased mercury remediation efficiency by 72.49%, compared to 38.1% without an static magnetic field and soil bioaugmentation. This study highlights the potential of combining an static magnetic field with microbial bioremediation to accelerate the remediation of mercury-contaminated soils, suggesting that this approach may become increasingly important in the future.